TEMPERATURE-DEPENDENT CORROSION OF AISI 1020, AL 1050, AND RIVETED JOINTS IN LANDFILL LEACHATE - Gunawan, Gunawan; Hadi, Qomarul; Ramadhani, Muhammad Iqbal (Asosiasi Peneliti Sriwijaya, 2025)
Corrosion is a critical degradation mechanism for metallic materials operating in aggressive environments such as landfills, where chloride-rich leachate, high moisture, and fluctuating temperatures accelerate electrochemical reactions. This study investigates the corrosion behavior of AISI 1020 carbon steel, Al 1050 aluminium, and their riveted joints under simulated landfill conditions at 30 °C, 40 °C, and 50 °C using the weight-loss method in accordance with ASTM G31-72. The landfill leachate used in this research contained high chloride, BOD, and COD levels, representing a chemically and biologically aggressive medium. Results show that AISI 1020 and Al 1050 experienced the highest corrosion rate at the early immersion stage (day 2), followed by passivation and a significant rate reduction by days 4 and 6. Increasing temperature accelerated initial corrosion for all materials, with Al 1050 showing greater susceptibility due to chloride-induced breakdown of its passive film. Riveted joints displayed much higher and less stable corrosion rates than single-material specimens, especially at elevated temperatures. Galvanic coupling between steel and aluminium, combined with crevice geometry at the rivet interface, intensified localized attack and disrupted protective oxide films. The most severe corrosion occurred in Al 1050 with riveted joints at 50 °C, reaching 0.523 mm/year on day 2. These findings highlight the combined roles of galvanic and crevice corrosion in riveted assemblies under landfill conditions and emphasize the need for careful material selection and joint design in waste management systems.